IMPLEMENTATION OF THE TEACCH (TREATMENT AND EDUCATION OF AUTISTIC AND RELATED COMMUNICATIONS-HANDICAPED CHILDREN) METHOD IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT AGAPE WONOSOBO INCLUSIVE ELEMENTARY SCHOOL - Panca Wisnu Wardani; Rifqi Muntaqo; Mukromin (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2026)
This study aims to describe the implementation of the Treatment and Education of Autistic and Related Communications-Handicapped Children (TEACCH) method in Islamic Religious Education (PAI) learning at SD Inklusi Agape Wonosobo, as well as to identify the supporting and inhibiting factors in its implementation. This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the implementation of the TEACCH method at SD Inklusi Agape Wonosobo was realized through the use of structured visual aids, including picture cards, daily visual schedules, and projector media, integrated with lecture, storytelling, inquiry, and habituation methods. Learning was conducted in a repetitive and incremental manner to accommodate the limited long-term memory of autistic students. Evaluation was carried out continuously through daily material repetition with gradual content addition. Supporting factors included the availability of varied learning facilities and infrastructure, as well as the competence and dedication of educators in implementing differentiated and personalized instruction. The primary inhibiting factors stemmed from the characteristics of the students themselves, namely limited long-term memory retention and significant heterogeneity in individual comprehension abilities, which demanded intensive individualized attention. Nevertheless, through consistent repetition and patient guidance, students demonstrated meaningful learning outcomes, including the ability to memorize daily prayers independently without teacher assistance.